The Switch of Audit Conceptual Models and Transformation of its Definition at the Current Stage - A. I. Popova (Учёт. Анализ. Аудит, 2024)
The paper reveals four main stages of formation and development of the audit institute and shows the change of concepts: from confirmatory to system-oriented and from risk-based to crisis-oriented audit. The author analyzed their features and distinctive traits. The study’s aim is to form the latest concept of crisis-oriented audit applied in Russia and the world at the present stage. Also, the author has presented her model of this concept. Auditors in the scientific community widely employ metaphorical characteristics, including “watchdog” in confirmatory audit, “sniffer dog” in system-oriented audit, and “guide dog” in risk-based audit. Furthermore, auditors in a crisis-oriented audit introduce the concept of a “rescue dog” in the scientific community. The methodological basis of the research is the works of Russian and foreign authors. The paper systematized scientific approaches to the definition of “audit” first ever. The author examines the transformation of this definition depending on the development of the audit institution and the emergence of conceptually new audit paradigms. The study concludes that current definitions of “audit” and “digital audit” do not adequately address the challenges faced by the audit institution. The author proposes her own definition of these concepts in the crisis-oriented audit framework. The article also analyzes extra risks inherent in digital audit, both in relation to the auditor and in relation to the audited entity.